2014
DOI: 10.1186/1471-2458-14-700
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to HPV vaccination of young women in high-income countries: a qualitative systematic review and evidence synthesis

Abstract: BackgroundVaccination against Human Papillomavirus (HPV) is recommended for adolescent young women prior to sexual debut to reduce cervical cancer related mortality and morbidity. Understanding factors affecting decision-making of HPV vaccination of young women is important so that effective interventions can be developed which address barriers to uptake in population groups less likely to receive the HPV vaccine.MethodsWe undertook a qualitative systematic review and evidence synthesis to examine decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
211
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(219 citation statements)
references
References 65 publications
(210 reference statements)
3
211
0
5
Order By: Relevance
“…(12,13) A recent systematic review regarding barriers to and facilitators of HPV vaccination in young women in high-income countries showed that HPV vaccination uptake was determined by policymakers, healthcare professionals and parents. (14) Findings also suggested that young women are predominantly passive recipients No. of respondents of the HPV vaccine.…”
Section: Discussionmentioning
confidence: 83%
“…(12,13) A recent systematic review regarding barriers to and facilitators of HPV vaccination in young women in high-income countries showed that HPV vaccination uptake was determined by policymakers, healthcare professionals and parents. (14) Findings also suggested that young women are predominantly passive recipients No. of respondents of the HPV vaccine.…”
Section: Discussionmentioning
confidence: 83%
“…Generally, girls should be targeted for HPV vaccination before the onset of sexual activities. (37,49) However, the age of sexual debut among Ethiopian girls is not known.…”
Section: Hpv Vaccination Challenges In Ethiopiamentioning
confidence: 99%
“…La preocupación no resuelta de padres y pacientes con respecto a la seguridad de la vacuna constituyó el detonante de esta cadena de eventos. La falta de educación, la carencia de una adecuada comunicación y la ausencia de discusión con respecto a los beneficios y riesgos de la vacuna (11), configuró la interior de la población de El Carmen de Bolívar una barrera insalvable (12,13) que llevó al rechazo de la vacuna.…”
unclassified